Does the Debt Ratio Mediate the Effect of Liquidity Ratio and Profitability Ratio on Stock Returns?: Empirical Evidence on Wholesale and Retail Trade Sub-Sector Companies on the Indonesia Stock Exchange - Subagyo; Rudolf Lumbantobing (Global Writing Academica Researching & Publishing, 2023)
This study aims to analyze the mediating effect of the debt ratio on the effect of liquidity and profitability on stock returns. Stock prices and returns are one unit, so that to estimate stock prices and returns can be seen from the company's financial performance, through financial ratios such as liquidity ratios, profitability ratios, and debt or leverage ratios. Companies with good financial performance are expected to have good stock performance. This study used a sample of 31 public companies in the wholesale and retail trade sub-sector which were listed on the Indonesia Stock Exchange in the 2016-2020 period. Sampling of this research was based on purposive sampling technique. The data analysis technique used is tiered linear regression, path analysis, and the Sobel test. The results of this study indicate that the significant liquidity ratio has a negative effect on the debt ratio and the liquidity ratio does not have a significant negative effect on stock returns. The profitability ratio has a significant positive effect on the debt ratio which confirms the trade-off theory. The profitability ratio has a significant positive effect on stock returns, while the debt ratio has a significant negative effect on stock returns. The debt ratio is not significant to mediate the positive negative effect of the liquidity ratio on stock returns. Likewise, the debt ratio is not significant mediating the negative positive effect of profitability ratios on stock returns. The results of this study suggest that investors who expect high stock returns do not need to pay attention to the company's debt ratio, but rather pay attention to the company's liquidity and profitability.